Preparation and Characterization of Textural and Energetic Parameters of Common and Functionalized SBA-15 Mesoporous Silicas - Vargas, Diana P. (2010)
A set of SBA-15 ordered mesoporous silicas presenting different surface acidities was obtained by organo-functionalization. Amino and sulphonic groups were attached onto the silica surface in order to determine the influence of organo-functionalization with acidic and basic moieties on the adsorption properties of silica. Cephalexin, an antibiotic molecule characterized by its zwitterionic nature, was selected as the adsorbate. The obtained matrices were characterized by scanning electron microscopy, energy dispersive X-ray analysis and nitrogen adsorption isotherms at 77 K. Enthalpies of immersion into water, benzene and cephalexin solutions were measured by immersion calorimetry, and the cephalexin adsorption capacities of the different matrices were also determined. The structure of SBA-15 was conserved in the functionalized samples despite a noticeable reduction in the BET surface area, pore volume and pore size. It was found that the inclusion of amino groups promoted interaction between the adsorbent and adsorbate, thereby favouring the retention of cephalexin.